2021
DOI: 10.1002/cche.10470
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chemical composition and techno‐functional properties of oat cultivars

Abstract: Background and objectives The number of products made of oats is expanding continuously, which indicates the need for a more detailed methodology for the determination of its quality traits. The aim of this work was to characterize Hungarian oat cultivars by general wheat testing methods and to investigate the discriminatory power of these, as well as to study relationships between chemical composition and techno‐functional properties. Findings Oat cultivars showed different dehulling properties. Among composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…Naked oats flour results recorded 13.23% protein, 7.94% fat, 2.0%ash, 16.58% dietary fiber, 10.36% Insoluble fiber, 6.2 % soluble fiber and 5.12 % β-glucans. These results were in agreement with Youssef, et al, (2016) and Renáta et al, (2021). Main while, defatted coconut powder, results showed that it contains 21.95 % crude protein, 7.5 % crude,5.7fat%ash, 30.44% dietary fiber, 17.65% Insoluble fiber, 12.79% soluble fiber and 0.00 % β-glucans.…”
Section: Results and Discussion Chemical Composition Of Raw Materialssupporting
confidence: 92%
“…Naked oats flour results recorded 13.23% protein, 7.94% fat, 2.0%ash, 16.58% dietary fiber, 10.36% Insoluble fiber, 6.2 % soluble fiber and 5.12 % β-glucans. These results were in agreement with Youssef, et al, (2016) and Renáta et al, (2021). Main while, defatted coconut powder, results showed that it contains 21.95 % crude protein, 7.5 % crude,5.7fat%ash, 30.44% dietary fiber, 17.65% Insoluble fiber, 12.79% soluble fiber and 0.00 % β-glucans.…”
Section: Results and Discussion Chemical Composition Of Raw Materialssupporting
confidence: 92%
“…Examining the viscous properties measured in different matrices (in slurry or dough), it was seen that the changes measured with RVA and Mixolab devices pointed in the opposite direction and the extent of the changes was also different. This also pointed to the phenomenon that the developers of the methods, researchers, and we had mentioned several times, that the viscosity measurement in two types of systems can show completely different results even in untreated samples (Balet et al, 2019;Espinosa-Ramírez et al, 2021;Jaksics et al, 2022;Németh et al, 2021). At the same time, the question can become particularly exciting if we examine and try to understand the consequences of some treatments (in our case, the effect of heat).…”
Section: Characterization Of Mixing and Viscous Properties In Dough S...mentioning
confidence: 81%
“…Besides, oat can be also a part of gluten‐free diet by selecting appropriate varieties and by ensuring strict gluten‐free processing conditions. Oat has higher lipid content (6%–8%) than other cereals (2%–3%), with particularly high proportion of unsaturated and polyunsaturated fatty acids characterization and comparison of selected wheat (Németh et al, 2021; Schlörmann et al, 2020). Unlike other cereals, the endosperm and bran account for most of the total lipids in oat grain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare, the composition of BSG alongside unmalted barley and some common cereal and legume sources is shown in Figure ; though it should be noted that this is a comparison between a byproduct whose nutritional value has been enhanced by processing and unprocessed cereal and legume raw materials. As most of the starch present in the barley grains is removed during the brewing process, the dietary fiber content of BSG can range from 40 to 50%, , significantly higher than that of unmalted barley, wheat, and oat (9–20%) , and legume sources including pea (14–21%), , soy bean (21–25%), , and faba bean (11–28%) ,, The main fiber constituent in BSG is hemicellulose which comprises 20–40% of the total composition. , The hemicellulose fraction of BSG primarily consists of arabinoxylan, a dietary fiber which has been linked with potential health benefits such as prebiotic activity, improved glycemic control, and antioxidant activity. , Cellulose and lignin are the other abundant polysaccharides in BSG, whose contents can range from 16 to 29%, ,, and 12 to 28%, respectively. , β-glucan is also present in low levels, normally in the range of ∼1% w/w …”
Section: Bsg: a Nutrient-rich Brewing Byproductmentioning
confidence: 99%